Stress, individual differences, and social support - Chay, Y; Yue Wah Chay (1990)
﻿ This thesis is concerned with the role of individual differences in personality and social support in mitigating work-related stress. The model of work stress described by House (1981) served as a general theoretical framework for two questionnaire studies of white-collar workers carried out in the course of this research. The present work also draws upon the demand-discretion model developed by Karasek (1979). The first study was carried out with a sample (N=117) of employees and self-employed business men and women. The main aims were to investigate: (i) individual differences in perceived social support; (ii) the stress-buffering role of support resources in moderating work-related stress. The results showed significant differences in personality and work characteristics between the occupational groups. There was evidence of interactive relationships between nAch, extroversion and locus of control in predicting perceived social support. Work and non-work support showed different moderating effects on job stressors in relation to job satisfaction and GHQ. A negative buffering effect of social support on job demand was also found in the prediction of GHQ. The findings suggest the importance of investigating further the role of individual differences in the way people develop and access socially supportive networks. The main objectives of the second study were: (i) to extend, in longitudinal data, previous findings concerning the buffering role of social support and individual differences in mediating the stress-illness relationship; (ii) to test the Johnson demand-control-support model of work stress. Work-related demands, social support, personality traits, and psychological health were assessed among a group of new graduates (N=121) in their first year of employment. The results showed significant changes in the overall levels of perceived demand, work-related support and psychological well-being between Time 1 and Time 2, and replicated the stress-buffering effects of social support found in the first study. More importantly, the findings suggest that the efficacious moderating effects of supportive relationships is dependent on the timing and matching of "stressors" with specific support resources; work-related social support showed weaker stress-buffering effects at initial assessment but was significantly stronger in moderating job stressors at Time 2. Analyses of individual difference variables showed that neuroticism, locus of control, and individual preferences for particular types of work characteristics acted as moderator variables. Consistent with Karasek and Johnson's models, significant demand-discretion and demand-discretion-support interactions was also found. However, in some instances, the three-way demand-control-support interactions were not of the form predicted. Overall, the present studies provide further information concerning the stress-buffering role of social support and individual differences at work. Further research should also focus on the sequencing of the stress-support process in order to provide a clearer understanding of how supportive relationships moderate work-related demands.